MICRO, SMALL AND MEDIUM ENTERPRISES SUCCESS FACTORS IN THE LEAN MANUFACTURING PERSPECTIVE : A THEORETICAL REVIEW - HARKIM (CV KULTURA DIGITAL MEDIA, 2020)
The fact of the success of a corporation becomes a believable challenge when a business unit is determined to move forward. Multi-national scale companies or TNCs like Toyota Corporation see success factors from a philosophical perspective on lean manufacturing. Identification of unnecessary processes or waste in the production process. This paper theoretically wants to explore the possibility of applying lean manufacturing principles in the MSME industry. This becomes a quite interesting problem when MSMEs become an idol for a business model that is imagined immune to various uncertainties. With the literature review approach this paper will elaborate on various previous studies conducted by experts. The analysis will be presented descriptively according to a predetermined logic. The analysis shows that (a) Application of lean manufacturing principles is only an option for MSME managers or owners. (b) The principles of lean manufacturing cannot be applied as a whole to a MSME, but rather selected parts of those principles that are compatible with MSME conditions in Indonesia. (c) One of the success factors of an MSME is also determined by the implementation of lean manufacturing principles, in other words the lean principle can increase the likelihood of being a success factor in the MSME.